The New Localism - Katz, Bruce; Nowak, Jeremy (Journal of Economic Sociology, 2023)
The New Localism is a book about cooperation among the state, business and civil society, whose joint efforts, according to the authors, create the genetic code of social change today. The book provides an analysis of the development trajectories of three cities: Pittsburgh and Indianapolis in the United States, and Copenhagen in Europe. Through an exploration of the histories of these cities, Bruce Katz and Jeremy Novak illustrate the work of the new models of development, governance and financing. In addition to examining the historical context of the emergence of new localism, the authors endeavor to predict its future based on its successes and challenges. The Journal of Economic Sociology publishes the first chapter of the book, “Reimagined Power”, where the authors consider the evolving dynamic of power. They observe a shift from the vertically organized commandadministrative system towards a web of horizontal relations that connect diverse sectors of society—state (public), commercial (private) and noncommercial—within local communities. The authors contend that power in the future will rest with problem solvers, thus challenging the conventional notion of power as the ability to coerce or effectively influence individuals’ behavior and decisions.